2014
DOI: 10.1002/ecj.11603
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation and Inhibition of Arabidopsis Seed Germination with Repetitive Barrier Discharges Produced by Polarity‐Reversed Voltage Pulses

Abstract: SUMMARY This paper presents an experimental study of control of the germination of Arabidopsis seed with a barrier discharge produced by polarity‐reversed voltage pulses. 100 ns‐width polarity‐reversed pulses were applied to the seeds between plane electrodes covered by glass barriers. The electrode configuration allowed barrier discharge propagation along the seed surface at a relatively low voltage. After the discharge treatment, the seeds were incubated for 2 or 3 days to measure the germination rate. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…When using the plasma, it is very important to know and optimize the plasma exposure/activation time. Short exposures may induce weak effects, while long exposures may result in inhibition and can negatively affect the seed germination and development of the plants …”
Section: Introductionmentioning
confidence: 99%
“…When using the plasma, it is very important to know and optimize the plasma exposure/activation time. Short exposures may induce weak effects, while long exposures may result in inhibition and can negatively affect the seed germination and development of the plants …”
Section: Introductionmentioning
confidence: 99%
“…The germination rate and seedling growth rate increased with the DC electric field exposure. They also confirmed that the of stem length of the mature plant was affected by the exposing DC voltage polarity (Kadowaki and Kurisaka 2013). Huang et al reported that germination of tomato seeds was induced by exposure to AC electric field of 4-12 kV/cm in strength and also by exposure to magnetic field of 3-100 G with an irradiation period from 15 to 60 s. The germination of the seed increased 1.1-2.8 times compared with that of the control (without exposure).…”
Section: High-voltage Direct Stimuli On Seed For Germination Promotionmentioning
confidence: 55%
“…This also provides the opportunity to perform a visual check for plasma uniformity and reliable ignition, and to check that all seeds have the same plasma exposure to reduce variation. [21] If the plasma setup uses a gas flow, flow flushing is recommended for a sufficient time to establish the nominal gas conditions [9,23,85] before beginning the plasma treatment of the seeds and to avoid the accumulation of RONS between replicates. Additionally, flow flushing also helps to reduce the effect of humidity on DBD electrodes (see Section 3.2).…”
Section: Experiments Designmentioning
confidence: 99%
“…DBDs generally work in the kilohertz range, although experiments can operate from 50 Hz [13,19,31,39,45,63,104,110,116] to 30 kHz [47] and up to nanopulse frequencies. [17,[21][22][23]91] Plasma jets have been operated from 500 Hz in AC bipolar square waveform, [101] to 58 kHz. [70,73] The continuous wave AC mode is preferentially implemented rather than the pulsed mode.…”
Section: Waveformmentioning
confidence: 99%
See 1 more Smart Citation